Searching the Appropriate Minimum Sample Size Calculation Method for Commuter Train Passenger Travel Behavior Survey - Anita Susanti; Ria Asih Aryani Soemitro; Hitapriya Suprayitno; Vita Ratnasari (Journal of Infrastructure & Facility Asset Management, 2019)
Commuter Train is one of the facilities that must be managed properly, economically and efficiently by the principles of Facility Asset Management. The availability of infrastructure and vehicles for this facility is adjusted based on passenger demand. This requires sufficient knowledge on the travel behavior characteristics, i.e., different characteristics composition proportion. Travel behavior survey requires the appropriate formula or method to calculate the minimum sample size, for this case are proportions of pq, pqr, pqrs etc. Therefore, a search for Minimum Sample Size Calculation Method for the Travel Behaviour Survey is needed. A literature study was employed for this search. This is important because the calculation method for the minimum sample size for proportions pq exists, but for the proportion of pqr, pqrs, etc do not yet exist. The results of the study indicates that the SR Method is the most appropriate method for calculating the minimum number of samples for the case of the proportion of pqr, pqrs, pqrst, etc. The SR Method is developed based on Goodnees of Fit method combined with the Maximum Acceptable Error principle. The combination of the two is named the MAECCL (Maximum Acceptable Error on a Certain Confidence Level) principle.